Genotipagem de amostras positivas para raiva em Mato Grosso e Rondônia, captura e identificação de morcego hematófago em Paranaíta-MT - Pimentel, Maria Fernanda Aranega (2023)
Rabies is a fatal disease that affects mammals, including humans. Despite not having effective treatment after the onset of symptoms, it can be prevented with vaccination. The incubation period is variable, causing non-suppurative meningoencephalitis. The etiological agent is an RNA virus of the genus Lyssavirus, which is distributed throughout the world, except in Antarctica. The conclusive diagnosis is made with samples of the central nervous system collected post mortem, and the standard diagnostic test is direct immunofluorescence. From 2005 to 2019, more than 49,000 cases of the disease were recorded in animals in Brazil, 3,418 of which were recorded in livestock in the state of Mato Grosso. The lack of information about the genetics, diversity and distribution of the rabies virus in Mato Grosso was the motivation for carrying out this study. A total of 117 brain tissue samples from cattle, horses, donkeys, mules and sheep from 29 municipalities in the state of Mato Grosso and one municipality in the state of Rondônia, collected between 2014 and 2021, were positive for the disease in the direct immunofluorescence test and/or biological tests. The genetic material was extracted and molecular analysis was performed using Reverse Transcriptase followed by Polymerase Chain Reaction for the N gene. Of the 117 samples analyzed, 50 were amplified by Reverse Transcriptase followed by Polymerase Chain Reaction, purified and sequenced, showing 93.13%–100% identity with the rabies virus. In the phylogenetic analysis, four clades were formed, which were genetically grouped in distinct regions within the Desmodus rotundus lineage. The results of clade geolocation will help to guide monitoring, control and health surveillance programs in MT. A specimen of the species Diphylla ecaudata that had no scientific record in the state of Mato Grosso was captured, identified and registered.